2016
DOI: 10.3389/fpsyg.2016.00713
|View full text |Cite
|
Sign up to set email alerts
|

Nosewitness Identification: Effects of Lineup Size and Retention Interval

Abstract: Although canine identification of body odor (BO) has been widely used as forensic evidence, the concept of nosewitness identification by human observers was only recently put to the test. The results indicated that BOs associated with male characters in authentic crime videos could later be identified in BO lineup tests well above chance. To further evaluate nosewitness memory, we assessed the effects of lineup size (Experiment 1) and retention interval (Experiment 2), using a forced-choice memory test. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…At retrieval, receivers immediately identified the target BO and only rated the perceptual features of the BOs after the identification (Alho et al, 2015), whereas in the present study, receivers only identified the target BO after providing the ratings to all the BOs included in the lineup. As a result, the time passed between encoding and retrieval may be slightly longer than 15 min, and in line with the findings by Alho et al (2016), incrementing the delay between encoding and retrieval may have a disruptive effect in the accuracy of the identification performance.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…At retrieval, receivers immediately identified the target BO and only rated the perceptual features of the BOs after the identification (Alho et al, 2015), whereas in the present study, receivers only identified the target BO after providing the ratings to all the BOs included in the lineup. As a result, the time passed between encoding and retrieval may be slightly longer than 15 min, and in line with the findings by Alho et al (2016), incrementing the delay between encoding and retrieval may have a disruptive effect in the accuracy of the identification performance.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, a methodological change implemented in the present study may have increased the difficulty of the recognition task when compared to Alho et al (2015Alho et al ( , 2016 and consequently reduced the accuracy performance. At retrieval, receivers immediately identified the target BO and only rated the perceptual features of the BOs after the identification (Alho et al, 2015), whereas in the present study, receivers only identified the target BO after providing the ratings to all the BOs included in the lineup.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations